ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI PASIR KENCANA KOTA PEKALONGAN - Sabana, Choliq; Suryani, Suryani; Madusari, Benny Diah; Pratikwo, Suryo; Hartati, Loso; Baroroh, Ida; Suraji, Imam; Satrio, Danang (JURNAL LITBANG KOTA PEKALONGAN, 2019)
This study entitled Potential Analysis and Development Strategy of Pasir Kencana Beach Tourism Object in Pekalongan City. The research objective to be achieved is to know and analyze the actual (physical and non-physical) aspects of tourism development in Pekalongan City beach attractions and analyze the development policy of coastal tourism objects in Pekalongan City as a strategy for planning Pekalongan City coastal tourism development and determining tourism development planning strategies sustainable tourism from coastal tourism objects in Pekalongan City in the context of developing coastal tourism. This research is descriptive, carried out to get a description or description of the assessment of aspects of the development of nautical tourism carried o ut through statistical calculations, then carried out an analysis of the development of attractions carried out using SWOT analysis techniques. Based on the objectives and results of the research conducted, conclusions can be drawn as follows: Overall, it can be concluded that the condition of the infrastructure and facilities of tourism at the Pasir Kencana Beach tourism location are still inadequate such as electricity networks and lighting, clean water networks, health facilities, facilities sanitation and hygiene, parking facilities, worship facilities, accommodation facilities, directions, which are still inadequate, and telecommunications networks, security facilities, financial facilities, business facilities, recreational facilities, information facilities and tourism services, tourism police and tourism units, souvenir shops, tourism information boards / tourist traffic signs, and landscape forms that are not yet available at the Pasir Kencana Beach tourism location.